Castor Frontline Demonstrations in Jodhpur District of Rajasthan : An Impact Study - M. Padmaiah, R. Venkattakumar, Ishwar Singh, S.S.Solanki and Ch. Sarada, (Indian Journal of Extension Education, 2022)
Jodhpur is one of the major castor growing districts in Rajasthan. More than150 frontline demonstrations (FLDs) were conducted by Agriculturral Research Station (ARS), Mandor in Jodhpur district of Rajasthan during last 10 years (1997-98 to 2006-07) to demonstrate the improved castor production technologies that are suitable for that particular eco-system. An attempt was made to analyze the impact of the demonstration in vertical and lateral spread of the technology and the resultant improvement in yield and income of the castor growers. Twentry-five FLD and the corresponding non-FLD castor growers were selected through proportionate random sampling procedure. There was no significant difference between the FLD and non-FLD farmers in their knowledge, adoption and yield levels. This shows the impact of FLDs in lateral spread of the improved technologies of castor crop. The castor area of the district has increased by about five times and production by about six times during the period 2002-03 to 2006-07. The frontline demonstrations had an overall ex-post-facto impact of 26 per cent increase in yield and Rs. 12620/ha in net returns. The B:C ratio was 3.5 and 2.8 with improved technology and farmers' practices plots respectively. There is a vast scope available for increasing the yield levels of castor inthe district and the reservoir was projected. Non-availability of quality seeds is the major constraint encountered by the castor growers of the study area. There is a need for intensive extension efforts by department of agriculture, through constructive collaboration with Agricultural Research Station, Mandor, Krishi Vigyan Kendras and local Non-Governmental Organisations to improve the yield as well as the production levels of castor in Jodhpur district